Opinion seeking behaviour of healthcare providers in ambulatory cardiovascular care in Germany: a cross-sectional study - Patrick Hennrich; Christine Arnold; Pia Traulsen; Frank Peters-Klimm; Michel Wensing (BMC, 2022)
Abstract Background Healthcare providers' inclination to seek or lead other providers' opinions on clinical topics may influence healthcare practices, particularly regarding their alignment across different providers in controversial domains. This study aimed to explore opinion-seeking behaviours of general practitioners and their impacts on clinical opinions in ambulatory cardiovascular care in Germany. Methods Between 2019 and 2021, we performed a written survey in two samples of general practitioners and one sample of self-employed cardiologists in three German states. The general practitioners were asked to identify a person they deemed influential on their views on cardiovascular conditions. Their self-perceived opinion leadership and opinion seeking behaviours were then measured, using a validated 12-item-questionnaire. General practitioners and cardiologists were requested to indicate their agreement with three potentially controversial aspects of cardiovascular ambulatory care. Potential impacts on the general practitioners' views, including local cardiologists' opinions, were examined using multi-level linear regression models. Results A total of 129 general practitioners and 113 cardiologists returned the questionnaire. 68.50% of general practitioners named an opinion leader, mainly cardiologists outside of their practice. General practitioners perceived themselves as opinion seeking and as opinion leading at the same time. Views on the presented controversial topics were mixed among both general practitioners and cardiologists. Self-reported opinion leadership behaviour of general practitioners was associated with their views on one of the three topics. No such associations were found for opinion seeking behaviours and the views of local cardiologists. Conclusion While most general practitioners named a cardiovascular opinion leader and saw themselves as opinion seeking regarding cardiovascular issues, they simultaneously perceived themselves as opinion leading, suggesting that opinion leadership and opinion seeking are not mutually exclusive concepts. The views of local cardiologists were not associated with the general practitioners' view, suggesting that local medical specialists do not necessarily influence the surrounding opinion seekers' views per se. Trial registration: We registered the study prospectively on 7 November 2019 at the German Clinical Trials Register (DRKS, www.drks.de ) under ID no. DRKS00019219.